Alpha Rhythms in Audition: Cognitive and Clinical Perspectives - Weisz, Nathan; Hartmann, Thomas; Müller, Nadia; Obleser, Jonas (Frontiers in Psychology, 2011)
Like the visual and the sensorimotor systems, the auditory system exhibits pronounced alpha-like resting oscillatory activity. Due to the relatively small spatial extent of auditory cortical areas, this rhythmic activity is less obvious and frequently masked by non-auditory alpha-generators when recording noninvasively using MEG or EEG. Following stimulation with sounds, marked desynchronizations can be observed between 6-12 Hz, which can be localized to the auditory cortex. However knowledge about the functional relevance of the auditory alpha rhythm has remained scarce so far. Results from the visual and sensorimotor system have fueled the hypothesis of alpha activity reflecting a state of functional inhibition. The current article pursues several intentions: 1) Firstly we review and present own evidence (MEG, EEG, sEEG) for the existence of an auditory alpha-like rhythm independent of visual or motor generators, something that is occasionally met with scepticism. 2) In a second part we will discuss tinnitus and how this audiological symptom may relate to reduced background alpha. The clinical part will give an introduction into a method which aims to modulate neurophysiological activity hypothesized to underlie this distressing disorder. Using neurofeedback, one is able to directly target relevant oscillatory activity. Preliminary data point to a high potential of this approach for treating tinnitus. 3) Finally, in a cognitive neuroscientific part we will show that auditory alpha is modulated by anticipation / expectations with and without auditory stimulation. We will also introduce ideas and initial evidence that alpha oscillations are involved in the most complex capability of the auditory system, namely speech perception. The evidence presented in this article corroborates findings from other modalities, indicating that alpha-like activity functionally has an universal inhibitory role across sensory modalities.